Problematika trading Forex dalam perspektif hukum Islam - Zahro, Latifatuz (Maliki Interdisciplinary Journal, 2023)
Buying and selling is the transfer of ownership rights from the seller to the buyer. While foreign exchange is foreign currency such as US dollars, yuan, ringgits, and so on. Buying and selling of foreign exchange occurs because of the need for export and import. However, recently buying and selling foreign exchange has become a promising investment area. From the point of view of ordinary people, exchange rate values that change from time to time and cannot be ascertained indicate that there are elements of gambling (maysir), containing fraud (gharar), exploitation, speculation, and usury. This research is a qualitative research using comparative analysis method where data collection comes from journals, news, observation books, and interviews. From the results of the analysis it was found that foreign currency is equated with al-sharf. There are two laws in an Islamic perspective regarding the sale and purchase of foreign exchange either online or offline. The first law forbids and the second law allows. This is based on the process of foreign exchange transactions.